Graphene oxide electrodeposited electrode enhances start-up and selective enrichment of exoelectrogens in bioelectrochemical systems. Issue 1 (December 2017) - Alonso, R.; San-Martín, M.; Sotres, A.; Escapa, A.
Abstract This study seeks to assess the impact that the anodic electrodeposition of graphene oxide (GO) has on the start-up process and on the development of microbial communities on the anode of BESs. The GO electrodeposited electrodes were characterised in abiotic conditions to verify the extent of the modification and were then transferred to a bioelectrochemical reactor. Results showed that the modified electrode allowed for a reduced start-up time compared to the control electrode. After three months, high throughput sequencing was performed, revealing that electrochemically reduced graphene oxide acts as a selective agent toward exoelectrogenic bacteria asGeobacter . Overall, this study shows that GO modified electrodes enhance biofilm build up in BES.